Causes of disputes in Sri Lankan construction industry based on the procurement system used - Nawarathna, N.M.P.J.G.L.; Edirisinghe, V. (Colombo : Sri Lanka Association for the Advancement of Science, 2021)
The Sri Lankan construction industry is one of the main industries which contributes 7.7–8.0% Gross Domestic Product (GDP) towards the country’s economy and a considerable amount of employment opportunities. However, the complex nature and the different stakeholder involvement negatively contribute to the construction project efficiency due to the occurrence of the dispute. However, the project risks which were not assigned are in the early stage of the dispute continuum model in the construction projects. Risk allocation of the construction projects was done through the procurement systems. Therefore, the focus of this research was to investigate the causes of disputes based on the traditional and design and build procurement systems in the Sri Lankan construction industry. The method adopted was mixed-method research. There, semi-structured interviews from 10 construction industry professionals were conducted to contextualize the dispute causes with procurement systems. For validation, interview findings were presented through a questionnaire survey to 40 industry professionals and made them to categorize the dispute causes based on the procurement systems. Design errors, unrealistic expectations, inadequate/incomplete specifications, quality of design, availability of information, ambiguities in contract documents, tendering, risk allocation, and unforeseen changes are only relevant to the traditional procurement system. Several other disputes such as variations initiated by the owner, change of scope, payment delays, delays in work progress, weather, site conditions, time extensions, the financial failure of the contractor, and quality of work, are common dispute causes for traditional and design and build procurement systems. The research finding signifies that the dispute causes in a traditional procurement system immerged because of the employer, contractor, project, design, and contract documentation. In design and build contract, the disputes are mainly due to the design and the contract documentation of the project. Hence, the risk allocation of each procurement system has made the changes in dispute occurrence in construction projects. Therefore, the causes of disputes which can occur in using different procurement systems should consider when selecting a procurement system for a construction project.
Keywords: Construction Industry; Disputes; Procurement System